Responsible management education: The PRME global movement (Routledge, 2022)
The ebook will beOpen Access and made available on publication. Written by many of the key influencers at the Principles for Responsible Management Education (PRME), the book focuses on advancing sustainable development into education, research and partnerships at higher education institutions and, specifically, at business schools, with the purpose of educating responsible leaders for today and tomorrow. The book serves as a concrete source of inspiration for universities and other stakeholders in higher education on structures, processes and content for how to advance responsible management education and sustainable development. It articulates the importance of key themes connected with the circular economy, gender equality, anti-corruption, business for peace, anti-poverty and other topics that are related to the Sustainable Development Goals (SDGs). The book emphasizes the significance of local-global interaction, drawing on local action at management schools in combination with global knowledge exchange across the PRME community. In addition, the book clearly demonstrates the background, key milestones and successful achievements of PRME as a global movement by management schools in collaboration with a broader community of higher education professionals. It exemplifies action in various local geographies in PRME Chapters, PRME Working Groups and the PRME Champions work to advance responsible management education. The authors of the book are all globally experienced deans, professors, educators and students with a global outlook, who are united to advance responsible management education locally and globally. The book will be invaluable reading for university leaders, educators, business school deans and students wanting to understand and embed responsible management education approaches across their institutions and curricula
Keywords: 650; PRME; Principles for Responsible Management Education; Responsible management; Responsible management education; Sustainability; UN Global Compact; Führungskräfteentwicklung; Nachhaltigkeit; Corporate Social Responsibility; Welt